Sequelae After Involution of Superficial Infantile Hemangioma: Early Intervention with 595-nm Pulsed Laser Combined with 755-nm Long-Pulsed Alexandrite Laser versus Wait-and-See - Jiang JC; Xu Q; Fang S; Gao Y; Jin WW (Dove Medical Press, 2021)
Ji-Cong Jiang,1,* Qin Xu,2,* Shan Fang,3 Yu Gao,1 Wan-Wan Jin1 1Department of Dermatology, The Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University, Wenzhou 325027, Zhejiang Province, People’s Republic of China; 2The Second School of Medicine, Wenzhou Medical University, Wenzhou 325027, Zhejiang Province, People’s Republic of China; 3Institute of Photomedicine, Shanghai Skin Disease Hospital, Tongji University School of Medicine, Shanghai 200443, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wan-Wan Jin; Yu Gao Email jinwanwan0604@163.com; gaoyu0570@sina.comBackground and Objective: Infantile haemangioma (IH) is the most common benign tumor in children. At present, pulsed dye laser (PDL) has made great progress in the treatment of superficial IH, showing good safety and effectiveness. But some doctors think that superficial IH should choose to wait-and-see. However, studies have reported that most of the IH after resolution still has residual disease, and thickness seems to be an important factor. Therefore, the purpose of this study is to investigate the relationship between Sequelae and thickness after superficial IH involution. In addition, compare the Sequelae difference between 595-nm pulsed laser combined with 755-nm long-pulse alexandrite laser treatment and wait-and-see.Materials and Methods: This retrospective observational study included patients with superficial IH evaluated in the past 6 years and divided them into a laser group and an observation group.Results: The incidence of sequelae in the laser group was 44.6%, and the incidence of sequelae in the observation group was 69.5%. The incidence of Sequelae of superficial IH in the laser group was significantly lower than that in the observation group (χ2-test, χ2=10.790, P < 0.001). In the observation group, the average A scores of the three thickness subgroups (< 2mm, 2– 5mm, and > 5mm) were 4.38, 3.39, and 1.80, and there were significant differences in the A scores between the three groups (Kruskal–Wallis, p< 0.05). There is a significant difference in the A score between the laser group and the observation group in the superficial IH with a thickness of 2– 5 mm and> 5mm (Wilcoxon rank sum test, P< 0.05).Conclusion: This retrospective study showed that the degree of Sequelae of superficial IH after involution is related to its thickness. In addition, the early intervention of 595-nm pulsed laser combined with 755-nm long-pulse alexandrite laser can reduce the incidence and extent of sequelae.Keywords: pulsed dye laser, alexandrite laser, infantile hemangiomas, sequelae, wait-and-see, thickness